The Influence of Use of the Imla' Method on Student Learning Outcomes in the Subject of Reading Write Al-Qur'an at Private MTS Nahdhatul Islam Manceg - Rahman, Bayu; Rudi, Hasrian (Universitas Ibn Khaldun, 2023)
The aim of this research is to determine student learning outcomes in Al-Qur'an reading and writing subjects. before and after using the Imla' method and whether or not there is an influence of the Imla' method on student learning outcomes in the Al-Qur'an reading and writing course in class VIII at the Nahdhatul Islam Mancang Private MTs. This research uses quantitative experimental methods, with the research design used is a quasi-experimental design. The subjects in this research were school principals, teachers in the subject of reading Al-Qur'an sincerely and all class VIII students at MTs Nahdhatul Islam Mancang. This research obtained results that show that there is an influence on the Imla' method through the results of the difference in the average value of the experimental class of 84.70 after the application of student-made image media with the average value of the control class being 68.16. Meanwhile, through hypothesis testing using the T test The obtained t value is 72.17 with a significance of 0.000 < 0.005, so it is stated that there is an influence (Ha) accepted. After the implementation of the Imla' method, student learning outcomes in Al-Qur'an reading and writing subjects increased compared to previous results, after the implementation of the Imla' method it showed that there was an increase. The population used was 60 class VIII students. The research sample was 30 students in class VIIIA (experimental class) and 30 students in class VIIIB (control class).